Developing a Temperature-Inducible Transcriptional Rheostat in Neurospora Crassa - Muñoz-Guzman, F (American Society for Microbiology, 2023)
Heat shock protein (HSP)-encoding genes (hsp), part of the highly conserved heat shock response (HSR), are known to be induced by thermal stress in several organisms. In Neurospora crassa, three hsp genes, hsp30, hsp70, and hsp80, have been characterized; however, the role of defined cis elements in their responses to discrete changes in temperature remains largely unexplored. To fill this gap, while also aiming to obtain a reliable fungal heat shock-inducible system, we analyzed different sections of each hsp promoter by assessing the expression of real-time transcriptional reporters. Whereas all three promoters and their resected versions were acutely induced by high temperatures, only hsp30 displayed a broad range of expression and high tunability, amply exceeding other inducible promoter systems existing in Neurospora, such as quinic acid- or light-inducible ones. As proof of concept, we employed one of these promoters to control the expression of clr-2, which encodes the master regulator of Neurospora cellulolytic capabilities. The resulting strain fails to grow on cellulose at 25 degrees C, whereas it grows robustly if heat shock pulses are delivered daily. Additionally, we designed two hsp30 synthetic promoters and characterized them, as well as the native promoters, using a gradient of high temperatures, yielding a wide range of responses to thermal stimuli. Thus, Neurospora hsp30-based promoters represent a new set of modular elements that can be used as transcriptional rheostats to adjust the expression of a gene of interest or for the implementation of regulated circuitries for synthetic biology and biotechnological strategies. IMPORTANCE A timely and dynamic response to strong temperature fluctuations is paramount for organismal biology. At the same time, inducible promoters are a powerful tool for fungal biotechnological and synthetic biology endeavors. In this work, we analyzed the activity of several N. crassa heat shock protein (hsp) promoters at a wide range of temperatures, observing that hsp30 exhibits remarkable sensitivity and a dynamic range of expression as we charted the response of this promoter to subtle increases in temperature, and also as we built and analyzed synthetic promoters based on hsp30 cis elements. As proof of concept, we tested the ability of hsp30 to provide tight control of a central process, cellulose degradation. While this study provides an unprecedented description of the regulation of the N. crassa hsp genes, it also contributes a noteworthy addition to the molecular toolset of transcriptional controllers in filamentous fungi.